Community dynamics of Neocallimastigomycetes in the rumen of yak feeding on wheat straw revealed by different primer sets. (October 2019) - Wang, Xue-Wei; Benoit, Isabelle; Groenewald, Johannes Z.; Houbraken, Jos; Dai, Xin; Peng, Mao; Yang, Xu; Han, Da-Yong; Gao, Cheng; Guo, Liang-Dong
Abstract: Anaerobic fungi ( Neocallimastigomycetes ) play an important role in fermenting lignin-rich plant biomass into sugars in the rumen of animals, representing a very promising enzyme resource to contribute to the conversion of plant biomass into biofuels. However, current studies about their functions mainly focus on limited species, and little is known about the coordination of different members of the anaerobic fungi in the digestion process of plant fibres. In this study, the community composition of anaerobic fungi in the rumens of yaks at five different time points (1, 3, 5, 7.5 and 24 h after feeding wheat straw) was investigated employing a cultivation-independent method using ITS clone libraries. Comparison of five pairs of primers showed that PCR primer sets could have clear amplification bias and therefore potentially affect the interpretation of the resulting fungal community structure; then two primer sets GM1/MNGM2 and ITS1/ITS4 were selected. Among the 398 sequences from 10 clone libraries, 18 operational taxonomic units (OTUs) of Neocallimastigomycetes were obtained, covering five known genera and one yet uncultured lineage. OTUs belonging to the bulbous-type morphotype ( Caecomyces - or Cyllamyces -related) and the rhizoidal genus Neocallimastix were abundant and predominantly present, representing 62.7% and 19.3% OTUs respectively. In all the later samples taken from 3 h to 24 Neocallimastigomycetes h after feeding, a relatively stable community composition was revealed: members of Neocallimastix increased to represent 43.4–49.4% and the bulbous-type morphotype declined to represent 39.5–42.7%. This implies a substantial turnover and synergy between bulbous and rhizoidal morphotypes of anaerobic fungi during the process of fibre digestion. Our study provided the first insight into the in vivo temporal change in the anaerobic fungal community, and the role of Neocallimastigomycetes with a bulbous morphotype in the degradation of plant cell wall in the yak rumen.